(untitled) (Journal of Partial Differential Equations, 2025)
This paper studied a chemotaxis fluid coupled system which models the so-called “chemotactic Boycott effect”. Under certain inhomogeneous boundary conditions, we proved the existence of nontrivial steady state which depends only on one variable of such system in [0,1]^3. A positive lower bound of the oxygen concentration c was also obtained.